Composite Spiral Zone Plate - Shubo Cheng; Tian Xia; Mengsi Liu; Chenglong Zheng; Huaping Zang; Shaohua Tao (IEEE Photonics Journal, 2019)
A new kind of optical element, i.e., composite spiral zone plate (CSZP), is proposed to generate a twin-vortex beam along the optic axis in this paper. The axial diffraction property of the CSZP is analyzed theoretically and experimentally. The results demonstrate that the CSZP can possess two focused vortices with the same intensity peak, different topological charges, and customized axial positions. The proposed optical device exhibits significant potential for various applications including three-dimensional optical manipulation.